Entropy optimized Ferro-copper/blood based nanofluid flow between double stretchable disks: Application to brain dynamic - Shan Ali Khan; Sumeira Yasmin; Hassan Waqas; Emad A. Az-Zo'bi; Abdullah Alhushaybari; Ali Akgül; Ahmed M Hassan; Muhammad Imran (Alexandria Engineering Journal, 2023)
Researchers and scientists were inspired by the enormous reactions from industry about heat transformation enhancements due to the entropy generation. The entropy generation shows as a extremes for complex mechanisms like solid state physics, two-phase flows, electro-magnetic air conditioning, and economic evaluation of manufacturing processes, as well as biological technologies chemistry, including biochemistry. We note here that many thermal mechanisms are related to the irreversibility system. The current work focused on the entropy generation impacts in viscous magnetized mono-nanofluids flow between stretchable rotating disks. Ferro and copper are considered as nanoparticles and Blood as a base fluid. The Darcy-Forchheimer porous medium and joule heating effects are considered. For simplifying the current analysis, suitable transformation were introduced in the mathematical description to renovate the partial differential equations (PDE’s) into coupled ordinary ones. To solve the resulting ODEs well-known numerical algorithm bvp4c is used in Matlab in the light of Lobatto-IIIA formula. The consequence of sundry parameters against velocity components, pressure field, temperature distribution and entropy generation are described graphically.